A Mixed-Method Analysis of Inequalities Associated With Adverse Sexual and Reproductive Health Outcomes and the Requisite Interventions Among Young Women in Durban Informal Settlements, South Africa - Obasanjo Afolabi Bolarinwa; Tlou Boikhutso (Frontiers Media S.A., 2022)
BackgroundOver the years, positive sexual and reproductive health (SRH) outcomes have been made possible by a series of policies such as the Sustainable Development Goals, targeted toward different aspects of young women's SRH needs. Nevertheless, inequalities in the levels and trends of adverse SRH outcomes still exist in sub-Saharan Africa (SSA), including South Africa. Thus, this study examines the inequalities associated with adverse SRH outcomes among young women in Durban informal settlements, South Africa, using a mixed-method analysis and suggested requisite interventions to reduce or eliminate the disparity.MethodsA mixed-method sequential explanatory design was used to address the research question. First, a quantitative cross-sectional survey was conducted among 547 young women aged 18 to 24 years in four informal settlements in Durban, South Africa, between April and July 2021. Thereafter, twenty (20) key informant interviews were conducted among different participants but with the same study characteristics. The study's outcome variable was adverse SRH outcomes, including HIV, STIs and unintended pregnancy, while the independent variable was inequality. The quantitative analysis employed binary and multivariable analysis to determine the association between the outcome and explanatory variables, using an alpha level of p < 0.05 to determine significance, while the qualitative analysis was done thematically.ResultsAt the quantitative level, the prevalence of adverse SRH outcomes among young women dwelling in Durban informal 242 settlements were 17.55%, 9.14% and 18.10% for STIs, HIV and unintended pregnancy, respectively. The adjusted odds ratio showed that young women who ever discussed sexual matters with their parents had a lower likelihood of reporting having STIs [aOR = 0.20; 95% (CI = 0.15-1.01)], HIV [aOR = 0.20; 95% (CI = 0.15-1.01)] and unintended pregnancy [aOR = 0.20; 95% (CI = 0.15-1.01)] compared to young women who never had a sexual discussion with their parents. Almost all the key informant interview participants shared the same perspective and proffered possible solutions in the qualitative results.ConclusionThere are disparities in the factors associated with adverse SRH outcomes in Durban's informal settlements. Healthcare proximity, child support grants, cigarette smoking, alcohol consumption, polygamous family structures and gender based violence were associated with higher odds of reporting adverse SRH outcomes.